What is the link between endometriosis and adiposity? - Juyeon Hong; Kyong Wook Yi (Korean Society of Obstetrics and Gynecology, 2022)
Endometriosis is defined by the presence of extrauterine endometrial tissue and presents with symptoms of dysmenorrhea, chronic pelvic pain, and impaired fertility. This condition often follows a chronic progressive course with favorable recurrence, even after surgical or medical treatment. The etiology or exact pathophysiology of endometriosis remains to be clarified, although it is thought to be a complex and multifactorial disease. Prior epidemiological or population-based studies have reported several risk factors related to endometriosis, such as environmental, menstrual, habitual, and lifestyle factors. Moreover, anthropometry has been found to be significantly associated with the diagnosis of endometriosis, as a lower body mass index is associated with an elevated risk of endometriosis. Here, we review studies that have examined the association between body size and the risk of endometriosis and discuss the clinical and biological significance of the relationship between adiposity and endometriosis.